Só faltou o título - Pujol Filho, Reginaldo da Luz (2015)
This is a Creative Writing project, therefore it starts with a fictional narrative: Just the Title’s Missing (yes, this is the title), about which I will not offer any information because there are some readers who don’t like to know anything before reading; and because this is an abstract and not a book flap; and because some currently believe that it doesn’t matter what the author has to say about their book. But, even so, I would like to say that I not only see this project as a narrative but also as research into themes that are dear to me in the production of fiction and in the observation of the world. Just the Title’s Missing is followed by the essay The Boxed Writer – Or Who Wants to Be A Writer in Brazil and Other Questions for Characters Who Don’t Exist. This essay starts with my observation of some of the peculiarities of the character Edmundo Dornelles, the protagonist of Just the Title’s Missing. Such peculiarities reflect upon being a writer in Brazil, about this Boxed Writer image that I suggest and about other themes within the Brazilian literary field of the twenty-first century.